Clinical outcomes of non‐nasopharyngeal lymphoepithelial carcinoma treated with a combined modality approach: A single‐institution study. (4th December 2022) - Qiu, Zichen; Lin, Feifei; Lyu, Shaowen; Xie, Dehuan; Wang, Lei; Wu, Zheng; Cheng, Wanqin; Tao, Yalan; Su, Yong
Abstract: Background: This study presents a summary of the clinical characteristics of non‐nasopharyngeal lymphoepithelial carcinoma (NNPLEC), effects of combined modality treatment and prognostic value of plasma Epstein–Barr virus (EBV) deoxyribonucleic acid (DNA) load, with the aim of providing a reference framework for optimizing treatment practices and outcomes. Methods: Patients with NNPLEC treated by our center between January 2000 and December 2020 were retrospectively reviewed. Results: In total, 728 patients were included. The lung was identified as the most common primary tumor site (64.0%), followed by the salivary gland (19.2%). A total of 539 (74.0%) patients underwent surgery, 459 (63.0%) received chemotherapy, and 361 (49.6%) were subjected to radiotherapy. The median follow‐up time was 45 months (range, 6–212 months) and 5‐year overall survival (OS) was 79.1%. Increased plasma EBV‐DNA load of >513.5 copies/mL was predictive of disease progression, with a specificity of 98.1% and a sensitivity of 98.9%. In multivariate Cox analysis, N stage, surgery, and radiotherapy were independent prognostic factors for both OS and PFS. Radiotherapy significantly improves OS in comparison with no radiotherapy group for salivary LEC, while surgery significantly improves OS for pulmonary LEC. Conclusion: Based on our analysis, surgery and radiotherapy are associated with better OS and PFS for NNPLEC. Radiotherapy could be recommended for salivary LEC, while surgery remains the primary treatment strategy for pulmonary LEC patients. An increased plasma EBV‐DNA load of >513.5 copies/mL is strongly predictive of disease progression, supporting the importance of regular evaluation of plasma EBV‐DNA as part of the diagnostic routine.